STUDI SPASIAL KEBERADAAN BREEDING PLACES DENGAN KEJADIAN MALARIA DI DESA BULUDE KECAMATAN KABARUAN KABUPATEN KEPULAUAN TALAUD - Maya Tindige; Joy V.I. Sambuaga; Steven J. Soenjono (Jurnal Kesehatan Lingkungan, 2018)
The incidence of malaria is 350-500 million cases every year, with more than 1.1 million deaths the majority of deaths occur in pregnant women and children aged less than 5 years. Malaria is the number 4 cause of death in the world after respiratory infections, HIV / AIDS and diarrhea. The purpose of this study is to specialize and find out the relationship between Breeding places and the incidence of malaria in the Bulude Village, Kabaruan Sub-District, Talaud Islands Regency. The results of the study prove that the spread of malaria incidence in Bulude Village, Kabaruan Subdistrict, Talaud Islands Regency in 2017 is spatial, the physical environmental conditions (temperature and humidity) in the habitat of Anopheles sp. in malaria sufferer settlement areas in Bulude Village, Kabaruan Subdistrict, Talaud Islands Regency in 2017 are Temperature 26-290C, humidity 82% - 87%, Chemical environmental conditions (pH and salinity) in Anopheles sp. in malaria settlement areas in Bulude Village, Kabaruan Subdistrict, Talaud Islands Regency in 2017, the pH is in the range of 8-9.2 and salinity is 0%. Breeding Type places in Bulude Village, Kabaruan Subdistrict, Talaud Islands Regency in 2017 consists of Puddles / Ditches, Rivers and marshes and there is no relationship between the existence of breeding places and the incidence of malaria in Bulude Village, Kabaruan Subdistrict, Talaud Islands District, 2017 p = 1.00. It is recommended for the public to pay attention and increase awareness of what can cause malaria and to carry out malaria prevention activities such as cleaning the environment routinely at least once a week